Interview with Eddie Reisch - Hazel Owen (Flexible Learning Association of New Zealand, 2013)
Eddie Reisch is currently working as a policy advisor for Te Reo Māori Operational Policy within the Student Achievement group with the Ministry of Education in New Zealand, where he has implemented and led a range of e-learning initiatives and developments, particularly the Virtual Learning Network (VLN). He is regarded as one of the leading innovators in the area of blended learning in K-12, and during his 30 years in education he has applied an unwavering belief that all learners can be the best they can when empowered to collaborate, make choices, be creative, and learn from their mistakes. Eddie was interviewed by Hazel Owen, Director of Ethos Consultancy NZ on 10 January 2013.